Designing an innovation sourcing process : A case study in the pharmaceutical industry - Valtonen, Pinja (My University, 2020)
This research was conducted as an assignment for a Finnish pharmaceutical company, Orion Corporation. Innovations have become increasingly important for organizations’ growth efforts. Particularly in the pharmaceutical industry, companies must generate innovations to sustainably increase the bottom line due to substantial pressures to lower prices. Thereby, also procurement literature has increasingly focused on highlighting the criticality of exploiting suppliers’ knowledge for increased innovation performance. Also in practice, procurement functions have recognized their significant role in enabling innovations. However, thus far, research regarding innovations in procurement focuses mainly on the supplier relationship management (SRM) process, which encompasses actions within the current supplier base. While these research contributions are valuable for emphasizing the importance of innovation efforts with suppliers, the current academic literature lacks in understanding how innovations can be driven with an aligned sourcing process. Thus, the aim of this research was to develop a case company specific innovation sourcing process and to define when to adopt the developed process. To address the research aims, relevant research disciplines were first examined to develop a theory based process and a propositional application context. To examine practical applications, four large Finnish companies that have already implemented an innovation sourcing process were interviewed. Subsequently, the researcher facilitated three interactive case company workshops. As a result, a case company specific innovation sourcing process was constructed based on the findings from theory, the benchmarked company processes and the workshops. To assess the applicability of the process and when it should be adopted, case company sourcing managers responded to a questionnaire regarding the likelihood of applying the process and the foreseen challenges. The final process comprises of five main phases: define, discover, ideate, test & develop MVP (Minimum Viable Product) and transfer. The process is characterized by substantial iteration and end user centricity in contrast to the traditional sourcing process. The average likelihood of applying the process was 3.7/5, indicating the acceptance of the process. Furthermore, regarding the applicable sourcing context, two key determinants, solution specification, and company and sourcing case attractiveness, were identified. Consequently, these determinants were incorporated into a case company specific evaluation matrix which sourcing managers can utilize when assessing the applicability of the innovation sourcing process.

Tämä tutkimus on tehty toimeksiantona suomalaiselle lääketeollisuusyhtiölle, Orion Oyj:lle. Innovaatioiden tärkeyttä korostetaan yhä enemmän yhtiöiden kasvutekijänä. Tämä korostuu lääketeollisuudessa kasvavan hintakilpailun johdosta. Täten yritysten on jatkuvasti kehitettävä uusia innovaatioita kannattavuutensa puolustamiseksi. Hankinnan kirjallisuudessa korostetaan enenevissä määrin toimittajien tietotaidon hyödyntämistä innovaatioiden edistämisessä. Lisäksi käytännössä yritysten hankintaorganisaatiot ovat tunnistaneet merkittävän roolinsa innovaatioiden mahdollistamisessa. Hankinnan tutkimus innovaatioiden edistämisestä keskittyy kuitenkin pääasiassa toimittajahallintaprosessiin, joka kattaa toimet yrityksen nykyisten toimittajien kanssa. Aiemmat tutkimustulokset ovat arvokkaita, sillä ne korostavat toimittajien tietotaidon hyödyntämistä innovaatioiden edistämisessä. Toisaalta kirjallisuudessa on tutkimusaukko kilpailutusprosessin kehittämisen osalta. Täten tässä tutkimuksessa kehitettiin toimeksiantajalle soveltuva innovaatiokilpailutusprosessi ja määritettiin, milloin tai millaisiin hankintaprojekteihin tätä tulisi soveltaa. Tutkimusaukon johdosta kirjallisuudesta ei löytynyt valmista mallia innovaatiokilpailutusprosessista. Täten tutkimuksessa kehitettiin ensin teoreettinen malli eri tieteenalojen kirjallisuuden pohjalta. Kirjallisuuskatsauksen tuloksena syntyi ehdotus prosessin soveltamiskontekstista. Teorian tueksi haettiin esimerkkiprosesseja käytännöstä. Tutkija haastatteli hankinta-ammattilaisia neljässä suuressa suomalaisessa yhtiössä, jotka ovat jo ottaneet käyttöön vastaavanlaisen prosessin. Tämän jälkeen tutkija fasilitoi kolme interaktiivista työpajakertaa, johon osallistui asiantuntijoita toimeksiantajayrityksen hankinta- ja liiketoimintaorganisaatioista. Työpajoissa kehitettiin toimeksiantajalle soveltuva innovaatiokilpailutusprosessi teorian ja käytännön löydösten pohjalta. Lisäksi prosessin soveltamiskontekstia selvitettiin kyselyllä, joka lähetettiin kaikille toimeksiantajan hankintapäälliköille. Kysely kartoitti prosessin soveltamisen todennäköisyyttä ja ennakoituja käytännön haasteita. Lopullinen prosessi koostuu viidestä vaiheesta: määrittele, etsi, ideoi, testaa ja kehitä MVP (Minimum Viable Product), ja siirrä. Prosessissa korostuu iteratiivisuus ja loppukäyttäjäkeskeisyys perinteiseen kilpailutusprosessiin verrattuna. Keskiarvo prosessin soveltamistodennäköisyydelle oli 3,7/5, mikä viittaa prosessin hyväksymiseen. Lisäksi prosessin soveltamiseen liittyen tunnistettiin kaksi keskeistä tekijää: ratkaisun spesifikaatio sekä yrityksen ja projektin houkuttelevuus. Näiden tekijöiden pohjalta kehitettiin case-yrityskohtainen matriisi, jota hankintapäälliköt voivat hyödyntää arvioidessaan innovaatiokilpailutusprosessin soveltamista.
Keywords: innovations, sourcing process, pharmaceutical industry, process design, innovaatiot, kilpailutusprosessi, lääketeollisuus, prosessikehitys